2018
DOI: 10.1016/j.omto.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Oncograms Visualize Factors Influencing Long-Term Survival of Cancer Patients Treated with Adenoviral Oncolytic Immunotherapy

Abstract: The first US Food and Drug Administration (FDA)- and EMA-approved oncolytic virus has been available since 2015. However, there are no markers available that would predict benefit for the individual patient. During 2007–2012, we treated 290 patients with advanced chemotherapy-refractory cancers, using 10 different oncolytic adenoviruses. Treatments were given in a Finnish Medicines Agency (FIMEA)-regulated individualized patient treatment program (the Advanced Therapy Access Program [ATAP]), which required lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…[18][19][20] Much evidence shows that lncRNA is involved in many biological processes, such as cancer cell proliferation, apoptosis, invasion, and so on. [21][22][23][24][25][26] Moreover, because of their genome-wide expression patterns in a variety of tissues and their tissue specific expression characteristics, lncRNAs hold strong promise as novel biomarkers and therapeutic targets for cancer. [27][28][29][30] lncRNA OIP5 antisense RNA 1 (OIP5-AS1), a prominent tumorassociated lncRNA, contributes to intricate cellular mechanisms during tumorigenesis and development of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Much evidence shows that lncRNA is involved in many biological processes, such as cancer cell proliferation, apoptosis, invasion, and so on. [21][22][23][24][25][26] Moreover, because of their genome-wide expression patterns in a variety of tissues and their tissue specific expression characteristics, lncRNAs hold strong promise as novel biomarkers and therapeutic targets for cancer. [27][28][29][30] lncRNA OIP5 antisense RNA 1 (OIP5-AS1), a prominent tumorassociated lncRNA, contributes to intricate cellular mechanisms during tumorigenesis and development of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Between 2007 and 2012, 290 advanced cancer patients were treated with 10 different oncolytic viruses (Table 4) totaling 821 treatments. A long-term follow-up of these patients has been published [5]. Treatments were given in the context of an individualized treatment program under the EU Advanced Therapies directive [5].…”
Section: Advanced Therapy Access Program (Atap)mentioning
confidence: 99%
“…A long-term follow-up of these patients has been published [5]. Treatments were given in the context of an individualized treatment program under the EU Advanced Therapies directive [5]. While many objective responses were seen, no definite conclusions regarding overall survival benefit can be drawn as no reliable control group was available.…”
Section: Advanced Therapy Access Program (Atap)mentioning
confidence: 99%
“…It is shown that overexpression of hsa-miR-497-5p can regulate the expression of Smad3 and lead to cell cycle arrest in the G0/G1 phase [25][26][27]. Overexpression of miR-497-5p can reduce the content of insulin receptors and induce insulin resistance in HFD-MES rats [28][29][30]. Furthermore, the expression of miR-497- hsa-miR-1258 hsa-miR-424-5p hsa-miR-139-3p hsa-miR-139-5p hsa-leHCC-7c-3p hsa-miR-511-5p hsa-miR-195-5p hsa-miR-326 hsa-miR-497 -5p hsa-miR-122 -3p hsa-leHCC-7c-5p hsa-miR-101-3p hsa-miR-30c-1-3p hsa-miR-125b-2-3p hsa-miR-99a-3p hsa-miR-130a-3p hsa-miR-29c-3p hsa-miR-378a-5p hsa-miR-24-1-5p hsa-miR-26b-3p hsa-miR-30e-3p hsa-miR-455-3p hsa-miR-125b-5p hsa-miR-26b-5p hsa-miR-99a-5p hsa-miR-378c hsa-miR-30a-3p hsa-miR-1295b-5p hsa-leHCC-7g-3p hsa-leHCC-7b-3p hsa-miR-29c-5p hsa-miR-505-3p hsa-miR-30c-2-3p hsa-miR-500b-3p hsa-miR-532-5p hsa-miR-501-3p hsa-miR-301a-3p hsa-miR-589-3p hsa-miR-222-3p hsa-miR-421 hsa-miR-19a-3p hsa-miR-500a-3p hsa-miR-501-5p hsa-miR-221-3p hsa-miR-589-5p hsa-miR-4326 hsa-miR-188-5p hsa-miR-1301-3p hsa-miR-219b-3p hsa-miR-93-5p hsa-miR-3677-3p hsa-miR-18a-5p hsa-miR-1180-3p hsa-miR-1226-3p hsa-miR-21-5p hsa-miR-877-5p hsa-miR-224-3p hsa-miR-760 hsa-miR-4661-5p hsa-miR-548d-3p hsa-miR-765 hsa-miR-1266-5p hsa-miR-7706 hsa-miR-452-3p hsa-miR-452-5p hsa-miR-1254 hsa-miR-3591-5p hsa-miR-6783-3p hsa-miR-4746-5p hsa-miR-7974 hsa-miR-6844 hsa-miR-3200 -3p hsa-miR-4758 -5p hsa-miR-4664 -3p hsa-miR-3662 hsa-miR-190b hsa-miR-224-5p hsa-miR-196b-5p hsa-miR-182-5p hsa-miR-216a-5p hsa-miR-10b-5p hsa-miR-216a-3p hsa-miR-10b-3p hsa-miR-183-3p hsa-miR-135a-5p hsa-miR-216b-5p hsa-miR-96-5p hsa-miR-217 hsa-miR-183-5p hsa-miR-3144-3p hsa-miR-1269a hsa-miR-1269b hsa-miR-4652-5p hsa-miR-105-5p hsa-miR-767-5p…”
Section: Introductionmentioning
confidence: 99%